Survey of network-layer anonymous communication protocols - Liangmin WANG; Xiaoling NI; Hui ZHAO (网络与信息安全学报)
An anonymous communication system is an overlay network built on the application layer and combining various privacy protection technologies such as data forwarding,content encryption,and traffic obfuscation to hide communication relationships between entities and forwarded contents.However,there is a deficiency in the balance between performance and security as an anonymous communication system operating over an overlay network.With the advance of the future internet architectures,it is possible to build an infrastructure-based anonymous communication system.Such anonymous communication systems design anonymity as network infrastructure services and provide encryption operations for routers,which can solve the part problem of scalability and performance limitations of anonymous network.They can also be called network-layer anonymous communication protocols.The existing network-layer anonymous communication protocols (LAP,Dovetail,Hornet,PHI and Taranet) were studied.The classification standard of network-layer anonymous communication protocols were introduced.Its innovation point and specific encryption ideas were briefly described,and how to keep balance between security and performance was analyzed.The shortcomings and advantages of these kinds of network anonymous communication protocols were also pointed out.Finally,the challenges faced in the development of anonymous communication systems and the problems that need to be studied in depth were proposed.